IVC Measurements in Critically Ill Patients with Acute Renal Failure - Rami Jambeih; Jean I. Keddissi; Houssein A. Youness (Critical Care Research and Practice)
Objective. To determine whether the inferior vena cava (IVC) measurement by bedside ultrasound (US-IVC) predicts improvement in renal function in patients with acute kidney injury (AKI). Design. Prospective observational study. Setting. Medical intensive care unit. Patients. 33 patients with AKI were included. Intervention. US-IVC was done on admission. The patients’ management was done by the primary teams, who were unaware of the US-IVC findings. Two groups of patients were identified. Group 1 included patients who were managed in concordance with their US-IVC (potential volume responders who had a positive fluid balance at 48 h after admission and potential volume nonresponders who had an even or negative fluid balance at 48 hours after admission). Group 2 included patients in whom the fluid management was discordant with their US-IVC. Measurements and Main Results. At 48 hours, Group 1 patients had a greater improvement in creatinine [85% versus 31%, p=0.0002], creatinine clearance (78±93% versus 8±64%, p=0.002), and urine output (0.86±0.54 versus 0.45±0.36 ml/Kg/h, p=0.03). Conclusion. In critically ill patients with AKI, concurrence of fluid therapy with IVC predicted fluid management, as assessed by bedside ultrasound, was associated with improved renal function at 48 hours. This trial is registered with ClinicalTrials.gov registration number: NCT02064244.